2022
DOI: 10.3390/fermentation8110587
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spring Maize Genotypes on Fermentation and Nutritional Value of Whole Plant Maize Silage in Northern Pakistan

Abstract: In the current study, we evaluated the growth, biomass yield, ensiling, and nutritional characteristics of spring maize genotypes grown under the climatic conditions of Northern Pakistan. Six promising spring maize genotypes were grown under uniform standard agronomic conditions in 72 plots (8 m × 10 m), blocked within three replicate fields. Maize crops were harvested at targeted dry matter (DM) content (33 g/100 g DM). Data were collected on plant phonological characteristics and biomass yield, and then the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
1
6
5
2
Order By: Relevance
“…These results demonstrated that the cultivar of DK301 had great and stable CP quality, which might be explained by genetic composure [ 37 , 38 ]. Similar variation in CP content among maize genotypes have been reported earlier studies [ 8 , 28 ].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…These results demonstrated that the cultivar of DK301 had great and stable CP quality, which might be explained by genetic composure [ 37 , 38 ]. Similar variation in CP content among maize genotypes have been reported earlier studies [ 8 , 28 ].…”
Section: Resultssupporting
confidence: 88%
“…The CP content (g/100 g) was greatest in Beijing (8.66), followed by Tianjin (8.57), Cangzhou (7.82), Liaoyuan (7.80) and Urumchi (7.35). The CP content of the maize silages in the current study was higher than the range of CP values (6.3 to 7.5 g/100 g) reported for different maize genotypes [ 28 ], which could be related to the early harvest stage selected in the present study. Nevertheless, the CP values were within the range (5.7 to 12.4 g/100 g CP) reported for WPSC in the meta-analysis of Khan et al 2015 [ 2 ] Meanwhile, the soluble protein contents, such as NPN and SCP, of WPSC planted in Beijing were higher ( P < 0.05) than other regions.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations